Correlation between Smoking and Dyslipidemia in Elderly Males: An Analytical Cross-Sectional Study - Narindar Kumar, Shafaq Nazia Shaikh, Atif Iqbal, Faima Rani Memon, Tazeem Hussain, Saima Rafique (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To investigate the association between smoking and dyslipidemia in elderly males while accounting for age, BMI, and alcohol use. Study design: Analytical cross-sectional study Place and Duration: This study was conducted at Bhitai Dental and Medical College Mirpurkhas from march 2021 to march 2022 Methodology: The research comprised 2,160 participants who were divided into 3 different groups: current smokers, non-smokers, & past smokers. The research excluded those who smoked just sometimes (one cigarette per day). This study separated smokers into four categories: light (26.7 pack-years), medium (426.7-90.5 pack-years), heavy (440.5-75.5 pack-years), and extremely heavy (455.5-165.5 pack-years).On the same day, a survey, physical examination, and laboratory study of blood samples were used to evaluate the study population. The person was assessed while wearing light clothes and no shoes, and anthropometric measures comprised height and body weight. Weight was divided by height squared (kg/m2) to get the BMI. Using established protocols in the clinical laboratory, an automated biochemistry analyzer measured the blood levels of total cholesterol, triglycerides, high-density lipid cholesterol, low- density lipid cholesterol, Apo protein B, and Lipoprotein. Result: When compared to present smokers, the levels of triglycerides and high-density lipid cholesterol among non-smokers and former smokers were statistically significantly different (P=0.001). Other variables, such as Age, body mass index, use of liquor, systolic and diastolic blood pressure, did not significantly differ between non-, past, and present smokers. In comparison to light smokers, moderate, heavy, and very heavy smokers more commonly displayed abnormal levels of TGs, Apo-B, and TC, while very heavy smokers less frequently displayed abnormal levels of low-density lipid cholesterol. It was unexpected to find that among very heavy smokers, aberrant Apo-B levels were seen more frequently than low-density lipid cholesterol levels. The prevalence of abnormal HDL-C and lipoprotein (a) was higher among light smokers. After accounting for alcohol, BMI, and age, smoking remained a significant independent threat fact for dyslipidemia (P = 0.032). Conclusion:The study revealed that smoking caused TGs and apoB levels to rise in elderly males, and HDL-C levels to decrease, making it an independent risk factor for dyslipidemia. Keywords: smoking, dyslipidemia, elderly, males